Photoelectrochemical Hydrogen Production from Water Using Copper‐based Chalcopyrite Thin Films - Shigeru Ikeda; Shogo Ishizuka (ChemElectroChem, 2024)
Abstract Copper (Cu)‐based chalcopyrite compounds are promising photoabsorber materials not only for solar cells but also for photoelectrochemical (PEC) systems for conversion of sunlight energy into chemical energy. PEC water splitting to generate hydrogen (H2) is one of the most advanced technologies in a PEC system for the use of Cu‐based chalcopyrite compounds. In this review, we firstly introduce crystallographic/energetic structures of Cu‐based chalcopyrite compounds in view of their applications to PEC water splitting. Explanations for the operation of PEC water splitting using semiconductor materials are then overviewed. Based on these backgrounds, studies on PEC H2 evolution over photocathodes based on CuInS2 and CuGaSe2 thin films that we have developed are reviewed in detail. For realizing efficient PEC H2 evolution over these thin films, surface modifications with an n‐type layer such as CdS and a catalytic site such as Pt deposit were found to be indispensable. Precise controls of p‐n heterointerfaces formed by introducing an n‐type layer should also be required to enhance PEC performance. Although PEC water splitting has not reached the required efficiency to be useful, effective combinations of appropriate surface and interface modifications should lead to further improvements of properties to be close to practical applications.